Penerapan Metode Kisah Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran SKI Kelas VIII MTs Al-Banna Pulau Banyak Tanjung Pura Langkat - Zasmah Lubis, M. Ali Mukhlis, Diani Syahfitri (Khazanah : Journal of Islamic Studies, 2023)
The problem of the reseach is the students low value so it needs to increase the learning outcomes. The purpose of the reseach is: first, to describe the implementation of the story method in the VIII class MTs Al-Banna Pulau Banyak Tanjung Pura Langkat, to know the increasing of students learning outcomes VIII class MTs Al-Banna Pulau Banyak Tanjung Pura Langkat before applying jigsaw learning models. Third, to know of the story method increasing the student learning outcomes in VIII MTs Al-Banna Pulau Banyak Tanjung Pura Langkat. The object of the reseach is the students of VIII class. The data analysis using in the reseach is the tes and non test. Based on the reseach result is story method increasing studens learning outcomes is the good by the student avarage score recapitulation in cycle I is 59% and the cycle II 100%. The value of persentase of class completeness after applying of the story method is 78% increase to 87%.